Revisiting walking as mobile place-making practice: a discursive perspective. Issue 1 (2nd January 2023) - Witte, Alexandra
Abstract: Embodied mobilities are an important factor in how people engage with their environment, and thus contribute to the formation, contestation, and affirmation of place. Walking is a mobile place-making practice that most people engage in on an almost daily basis and which has thus been frequently investigated in regards to the consumption and construction of place. These explorations have predominantly been focusing on urban contexts and frequently taken the perspective of the multisensory, corporeal, cognitive, and emotional. However, discursive notions of who walks where and how, and how these ultimately contribute to place-making in tourism have been largely left unexplored. Employing a mobile approach to ethnography, walking as place-making is here considered in the context of tourism, taking a discursive perspective. Drawing on two walking groups on the Cloudpass, one of the trails of China's Ancient Tea Horse Road in Yunnan, notions of legitimate walking practices and trails are explored in their discursive undercurrents, and resulting place-making practices are outlined in conjunction with these and the encountered 'realities' of the trails. Complex interactions between walking tourists' beliefs around norms and regulations of walking and walking trails, and the Cloudpass' official narratives come to the fore, resulting in concrete practices of affirmation and contestation of the trail's legitimacy within tourists' subscribed to value systems. Touristic walking emerges as a discursive place-making practice, mandating closer attention to be paid to the norms and regulations people subscribe to within touristic and recreational walking and their effects on how people engage with the places they walk. On the Cloudpass and the Ancient Tea Horse Road beyond, touristic walking practices informed by diverse discursive notions selectively strengthen narratives of place over others and concretely contribute to the trails' changing narratives and materialities over time. 摘要: 具身性移动是人们与环境互动的重要因素, 因此有助于地方的形成、竞争和确认。步行是大多数人几乎每天都在进行的一种移动的地方营造实践, 因此经常从地方消费和建设方面进行研究。这些探讨主要集中在城市脉络下, 并经常从多感官、物质、认知和情感的角度切入。然而, 关于谁走到哪里, 怎么走, 以及这些行为最终如何对旅游中的地点营造做出贡献的零散概念, 在很大程度上一直未被探讨。本文采用一种移动的民族志方法, 在这里以一种散漫的视角, 思考了旅游的背景下步行作为地方营造的实践。本文基于中国云南茶马古道上云渡口（Cloudpass）徒步路线的两个徒步团队, 以散漫的潜在话语探讨了合法性徒步实践的概念, 勾勒出这些路线上遇到的多重真实。徒步游客对步行和步行步道的规范和规则的信仰与云渡口（Cloudpass）的官方叙述之间的复杂互动呈现出来, 导致在游客所接受的价值体系中, 对该路线合法性的确认和争论的具体实践。旅游步行作为一种散漫的地方营造实践, 要求更密切地关注人们在旅游和娱乐徒步中广为接受的标准与规范, 以及这些标准与规范对人们如何与他们所徒步的地方互动的影响。在云山口几其他茶马古道徒步路线上, 旅游徒步活动受到不同的话语观念的启发, 选择性地强化了地方优于他者的叙述, 并确实促进了步道随着时间的推移而不断变化的叙述和物质状态